Adrenal function recovery after durable oral corticosteroid sparing with benralizumab in the PONENTE study - Menzies-Gow, Andrew (2022)
Background Oral corticosteroid (OCS) dependence among patients with severe eosinophilic asthma can cause adverse outcomes, including adrenal insufficiency. PONENTE's OCS reduction phase showed that, following benralizumab initiation, 91.5% of patients eliminated corticosteroids or achieved a final dosage ≤5 mg·day-1 (median (range) 0.0 (0.0-40.0) mg). Methods The maintenance phase assessed the durability of corticosteroid reduction and further adrenal function recovery. For ~6 months, patients continued benralizumab 30 mg every 8 weeks without corticosteroids or with the final dosage achieved during the reduction phase. Investigators could prescribe corticosteroids for asthma exacerbations or increase daily dosages for asthma control deteriorations. Outcomes included changes in daily OCS dosage, Asthma Control Questionnaire (ACQ)-6 and St George's Respiratory Questionnaire (SGRQ), as well as adrenal status, asthma exacerbations and adverse events. Results 598 patients entered PONENTE; 563 (94.1%) completed the reduction phase and entered the maintenance phase. From the end of reduction to the end of maintenance, the median (range) OCS dosage was unchanged (0.0 (0.0-40.0) mg), 3.2% (n=18/563) of patients experienced daily dosage increases, the mean ACQ-6 score decreased from 1.26 to 1.18 and 84.5% (n=476/563) of patients were exacerbation free. The mean SGRQ improvement (-19.65 points) from baseline to the end of maintenance indicated substantial quality-of-life improvements. Of patients entering the maintenance phase with adrenal insufficiency, 32.4% (n=104/321) demonstrated an improvement in adrenal function. Adverse events were consistent with previous reports. Conclusions Most patients successfully maintained maximal OCS reduction while achieving improved asthma control with few exacerbations and maintaining or recovering adrenal function.